Análise espacial da distribuição longitudinal de sementes de milho em uma semeadora-adubadora de precisão - Santos, Alessandro José Marques; Gamero, Carlos Antonio [UNESP]; de Oliveira, Rone Batista; Villen, Andréia Correa [UNESP] (My University, 2011)
In the operation of sowing with planter numerous factors interfere with the establishment of the plant stand, among them, the longitudinal distribution of seeds depending on the displacement speed can significantly affect crop productivity. The present study aimed the evaluation of longitudinal distribution of maize seeds in two different speeds of dislocation of a precision grain drill, through classical and geostatistics. A regular grid sample, totalizing 100 points in each area, was built with 10-meter distance among the points. Each sample point comprised 3.6m2 (1.8 x 2.0) where the percentage of acceptable, double and fail spacing among the plants was measured after sowing at 4.58 and 5.94 km h-1 speed of dislocation. Classical and geostatistics were used for data analyses. The percentage of acceptable and failed spacing has shown significant difference between 4.58 and 5.94 km h-1 speed. The results has shown absence of spatial dependence regarding the percentage of the studied spacing (acceptable, fail and double) at both speeds, showing that studies and statistical inferences can occur based on parameters of classical statistics for distances higher than the shortest one used in the sampling.
Spatial analysis of longitudinal distribution of maize seeds in a precision grain drill
Keywords: Classical statistics; Pure nugget effect; Seed distribution; Spatial variability